Simulation guided design of the MRcollar: a MR compatible applicator for deep heating in the head and neck region - Drizdal, Tomas; Sumser, Kemal; Bellizzi, Gennaro G; Fiser, Ondrej; Vrba, Jan; Rhoon, Gerard C van; Yeo, Desmond T B; Margarethus M Paulides (International journal of hyperthermia, 2021)
PURPOSE: To develop a head and neck hyperthermia phased array system compatible with a 1.5 T magnetic resonance (MR) scanner for noninvasive thermometry. METHODS: We designed a dielectric-parabolic-reflector antenna (DiPRA) based on a printed reflector backed dipole antenna and studied its predicted and measured performance in a flat configuration (30 mm thick water bolus and muscle equivalent layer). Thereafter, we designed a phased array applicator model ('MRcollar') consisting of 12 DiPRA modules placed on a radius of 180 mm. Theoretical heating performance of the MRcollar model was benchmarked against the current clinical applicator (HYPERcollar3D) using specific (3D) head and neck models of 28 treated patients. Lastly, we assessed the influence of the DiPRA modules on MR scanning quality. RESULTS: The predicted and measured reflection coefficients (S11) of the DiPRA module are below -20 dB. The maximum specific absorption rate (SAR) in the area under the antenna was 47% higher than for the antenna without encasing. Compared to the HYPERcollar3D, the MRcollar design incorporates 31% less demineralized water (-2.5 L), improves the predicted TC25 (target volume enclosed by 25% iso-SAR contour) by 4.1% and TC50 by 8.5%, while the target-to-hotspot quotient (THQ) is minimally affected (-1.6%). MR experiments showed that the DiPRA modules do not affect MR transmit/receive performance. CONCLUSION: Our results suggest that head and neck hyperthermia delivery quality with the MRcollar can be maintained, while facilitating simultaneous noninvasive MR thermometry for treatment monitoring and control.
Keywords: Magnetic Resonance Imaging; indukovaná hypertermie; krk; Hyperthermia, Induced; vytápění; Heating; lidé; magnetická rezonanční tomografie; Humans; magnetická rezonanční spektroskopie; hlava; Neck; phased array; Antenna; magnetic resonance; Magnetic Resonance Spectroscopy; SAR; Head; head and neck